2021 clinical trials update: Innovations in hemophilia therapy. Issue 1 (2nd November 2020) - Croteau, Stacy E.; Wang, Michael; Wheeler, Allison P.
Abstract: Therapies engineered to prolong clotting factor protein circulation time, manipulate the balance of pro‐coagulant and anti‐coagulant proteins, or introduce new genetic material to enable endogenous factor protein production dominate the clinical trial landscape of hemophilia. The availability of clotting factor concentrates and the establishment of primary prophylaxis have dramatically improved health outcomes for hemophilia patients. But, the burden of hemostatic therapy remains significant, and many barriers to consistent longitudinal use of prophylaxis exist. Several types of emerging therapeutics including engineered factor concentrates, substitutive therapies, rebalancing therapies, and gene transfer/editing all aim to reduce the challenges of current hemophilia treatment. Emerging treatment options may reduce treatment frequency or need for intravenous administration. They may also introduce new challenges in laboratory assessment of hemostasis. These novel therapies must not introduce significant new health risks and continue to support similar or improved outcomes. The potential ramifications of rebalancing the coagulation cascade, particularly in a stress or inflammatory state, or introduction of new genetic material are not trivial. The focus of this review is to provide an overview of active and recently completed clinical trials as well as emerging preclinical data investigating new therapeutic possibilities for hemophilia patients and potentially other rare bleeding disorders.